1996
DOI: 10.1021/om950830z
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of N2, H2, CO2, and Ethylene to a T-Shaped Rhodium(I) Core

Abstract: The new rhodium−dinitrogen complex Rh(N2)[HC(CH2CH2P(t-Bu)2)2] (2) was prepared by elimination of HCl with sodium hydride from the hydrido chloride HRh(Cl)[HC(CH2CH2P(t-Bu)2)2] (1). Complex 2 reacts with various small gaseous molecules, giving rise to the new complexes Rh(X)[HC(CH2CH2P(t-Bu)2)2], X = H2 (3), C2H4 (4), CO2 (5). The first 16 electron rhodium−carbon dioxide complex 5 is spectroscopically characterized. All the transformations are reversible in the presence of free nitrogen. The thermodynamic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
126
0
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 42 publications
(50 reference statements)
17
126
0
5
Order By: Relevance
“…[84] As such, they described the facile deprotonation of the PNP backbone at one of the methylene spacers, concomitant with the dearomatization of the pyridine ring, in the absence of CO. [85] Vitagliano and co-workers have shown that the dicationic complex [Pt (12 Ph )] (73) is a suitable starting compound for stoichiometric reactions that involve nucleophilic attack of alcohols or amines onto coordinated alkenes (e.g., ethene). [86,87] In a related study (Scheme 29), they demonstrated that the same complexes can act as catalysts for the codimerization of ethene and internal alkenes (also known as the hydrovinylation reaction).…”
Section: Palladium and Platinummentioning
confidence: 99%
See 1 more Smart Citation
“…[84] As such, they described the facile deprotonation of the PNP backbone at one of the methylene spacers, concomitant with the dearomatization of the pyridine ring, in the absence of CO. [85] Vitagliano and co-workers have shown that the dicationic complex [Pt (12 Ph )] (73) is a suitable starting compound for stoichiometric reactions that involve nucleophilic attack of alcohols or amines onto coordinated alkenes (e.g., ethene). [86,87] In a related study (Scheme 29), they demonstrated that the same complexes can act as catalysts for the codimerization of ethene and internal alkenes (also known as the hydrovinylation reaction).…”
Section: Palladium and Platinummentioning
confidence: 99%
“…[11] Typical examples include frameworks 1-5 ( Figure 1). [12][13][14][15][16][17][18][19][20][21] Reviews on recent developments of these innocent monoanionic tridentate ligand systems, in particular those that carry a central amido functionality, are available. [10,22] Formally neutral tridentate ligand systems have seen a surge in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…[74] In ganz ähnlicher Weise wurde ein sehr ungewöhnlicher Rhodiumkomplex mit dem sperrigen starren Li [76] und konnten lediglich in situ durch Ligandendissoziation [77] oder Haptizitätswechsel [78] hergestellt werden. Ansonsten gehen diese Komplexe leicht in Chlor-verbrückte Dimere über, selbst beim Vorhandensein zweier sehr sperriger Liganden L. [79] das Chlorid abstrahiert.…”
Section: Koordinationsverhaltenunclassified
“…[84] Sie beobachteten die Deprotonierung des PNP-Rückgrats an einer der Methylengruppen, die mit der Desaromatisierung des Pyridinrings einhergeht, in Abwesenheit von CO. [85] Vitagliano und Mitarbeiter haben gezeigt, dass der dikationische [Pt (12 Ph )]-Komplex 73 für stöchiometrische Reaktionen geeignet ist, bei denen Alkohole oder Amine nucleophil mit koordinierten Alkenen reagieren (z. B. mit Ethen).…”
Section: Palladium Und Platinunclassified